2020
DOI: 10.1016/j.cherd.2020.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Selection criteria of diluents of tri-n-butyl phosphate for recovering neodymium(III) from nitrate solutions

Abstract: Selection of diluents considering extraction, cost, safety and biodegradability criteria

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 46 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…26 While aliphatic diluents typically enable significantly better extraction than aromatic solvents, studies by Regadı ´o et al found that mixed diluents with both aliphatic and aromatic components performed only slightly worse than the pure aliphatic mixtures. 27 This suggests that diluent effects are complex and nonlinear, indicating that empirical approaches such as solubility parameters derived from mixing rules 28 are not sufficient to capture actual behavior. Poirot et al examined solvent effects from the perspective of solvent structuring and the resultant effect on energetics.…”
Section: Introductionmentioning
confidence: 99%
“…26 While aliphatic diluents typically enable significantly better extraction than aromatic solvents, studies by Regadı ´o et al found that mixed diluents with both aliphatic and aromatic components performed only slightly worse than the pure aliphatic mixtures. 27 This suggests that diluent effects are complex and nonlinear, indicating that empirical approaches such as solubility parameters derived from mixing rules 28 are not sufficient to capture actual behavior. Poirot et al examined solvent effects from the perspective of solvent structuring and the resultant effect on energetics.…”
Section: Introductionmentioning
confidence: 99%